2018
DOI: 10.1080/21695717.2018.1519144
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of infant hearing screening from a developing country context

Abstract: Purpose: To explore the feasibility of infant hearing screening from a developing country context. Methods: A descriptive research design was employed, using a combination of surveys, questionnaires and face-to-face semi-structured interviews; as well as conduction of audiological measures such as otoacoustic emissions (OAEs) and automated auditory brainstem responses (AABR) during hearing screening. Participants comprised low–risk neonates, high-risk n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Current study findings indicated a higher specificity at the repeat hearing screening when compared to the initial hearing screening, for both OAE measures in isolation or in combination. These findings correlate with those in the larger study by Kanji (2016) which included the use of AABR technology.…”
Section: Discussionsupporting
confidence: 88%
“…Current study findings indicated a higher specificity at the repeat hearing screening when compared to the initial hearing screening, for both OAE measures in isolation or in combination. These findings correlate with those in the larger study by Kanji (2016) which included the use of AABR technology.…”
Section: Discussionsupporting
confidence: 88%
“…In India, there is no routine hearing screening test for children (Vaidyanath and Yathiraj, 2014;Ramkumar, 2017). Kanji et al (2018) showed that in South Africa, there are still many barriers to efficient infant hearing screening. Shinn et al (2019) reported that in rural areas of Kenya, ambient noise levels during hearing screening were so high that there were many false-positive referrals.…”
Section: Introductionmentioning
confidence: 99%
“…This may include revising the step 1 protocol by switching from TEOAE to aABR for all infants, adding a rescreen before discharge (either with the same technology or with aABR after a failed OAE), or by moving step 1 screen to an outpatient setting. Moving step 1 to an outpatient setting can improve referral rates if inpatient screening is performed only hours after birth [65]; however, policymakers must also consider whether these factors could affect the sensitivity of the screening programme and whether coverage rates will be negatively affected by such a reorganisation [66].…”
Section: Discussionmentioning
confidence: 99%